Dhofar 225 and Dhofar 735: relationship to CM2 chondrites and metamorphosed carbonaceous chondrites, Belgica-7904 and Yamato-86720 - Ivanova, Marina A.; Lorenz, Cyrill A.; Nazarov, Mikhail A.; Brandstaetter, Franz; Franchi, Ian A.; Moroz, Lyuba V.; Clayton, Robert N.; Bychkov, Andrew Yu (Meteoritics & Planetary Science, 2010)
Dhofar (Dho) 225 and Dho 735 are carbonaceous chondrites found in a hot desert and having affinities to Belgica-like Antarctic chondrites (Belgica [B-] 7904 and Yamato [Y-] 86720). Texturally they resemble CM2 chondrites, but differ in mineralogy, bulk chemistry and oxygen isotopic compositions. The texture and main mineralogy of Dho 225 and Dho 735 are similar to the CM2 chondrites, but unlike CM2 chondrites they do not contain any (P, Cr)-sulfides, nor tochilinite 6Fe 0.9 S*5(Fe,Mg)(OH) 2 . H 2 O-contents of Dho 225 and Dho 735 (1.76 and 1.06 wt%) are lower than those of CM2 chondrites (2-18 wt%), but similar to those in the metamorphosed carbonaceous chondrites of the Belgica-like group. Bulk compositions of Dho 225 and Dho 735, as well as their matrices, have low Fe and S and low Fe/Si ratios relative to CM2 chondrites. X-ray powder diffraction patterns of the Dho 225 and Dho 735 matrices showed similarities to laboratory-heated Murchison CM2 chondrite and the transformation of serpentine to olivine. Dho 225 and 735's oxygen isotopic compositions are in the high 18 O range on the oxygen diagram, close to the Belgica-like meteorites. This differs from the oxygen isotopic compositions of typical CM2 chondrites. Experimental results showed that the oxygen isotopic compositions of Dho 225 and Dhofar 725, could not be derived from those of typical CM2 chondrites via dehydration caused by thermal metamorphism. Dho 225 and Dho 735 may represent a group of chondrites whose primary material was different from typical CM2 chondrites and the Belgica-like meteorites, but they formed in an oxygen reservoir similar to that of the Belgica-like meteorites.